2018
DOI: 10.1016/j.fsi.2017.11.046
|View full text |Cite
|
Sign up to set email alerts
|

Glucan-MOS ® improved growth and innate immunity in pacu stressed and experimentally infected with Aeromonas hydrophila

Abstract: We tested the efficacy of a commercial product (Glucan-MOS) derived from yeast Saccharomyces cerevisiae, containing two combined products, β-1,3-1,6 glucans and mannans on the growth, feed efficiency, stress and innate immune responses of juvenile pacu (Piaractus mesopotamicus) after a stressful handling and bacterial inoculation. For this, we evaluated the serum cortisol and plasma glucose levels, the respiratory activity of leukocytes, the serum lysozyme levels, as well as the number of circulating erythrocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 41 publications
2
11
0
1
Order By: Relevance
“…Similarly, in P. mesopotamicus has been demonstrated that supplementation with 0.1 or 1.0% β-glucan, respiratory burst of leukocytes, complement hemolytic activity, lysozyme activity and number of leukocytes increased after challenge with A. hydrophila, reducing fish mortality [25]. The addition of 0.2 and 0.4% of Glucan-MOS ® was also sufficient to positively influence these immune parameters in P. mesopotamicus after challenge of stress and infection with A. hydrophila [10]. In E. coioides supplemented with different concentrations of S. cerevisiae and challenged with inoculation of Streptococcus sp.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Similarly, in P. mesopotamicus has been demonstrated that supplementation with 0.1 or 1.0% β-glucan, respiratory burst of leukocytes, complement hemolytic activity, lysozyme activity and number of leukocytes increased after challenge with A. hydrophila, reducing fish mortality [25]. The addition of 0.2 and 0.4% of Glucan-MOS ® was also sufficient to positively influence these immune parameters in P. mesopotamicus after challenge of stress and infection with A. hydrophila [10]. In E. coioides supplemented with different concentrations of S. cerevisiae and challenged with inoculation of Streptococcus sp.…”
Section: Discussionmentioning
confidence: 98%
“…The previous studies indicated that S. cerevisiae-based products were efficient in promoting fish growth and potentially viable for aquaculture use from the production viewpoint. Physiological indicators of health [6,16] and immune status [2,6,10] are often used to evaluate the efficacy of dietary supplementation of feed additives. In the current study, VSI and HSI of A. gigas fed with different Aquate Fish™ ® levels were not altered, although plasma triglycerides, cholesterol and glucose increased in fish fed 12 g Aquate Fish™ ® .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the mannose present in MOS particles can be recognized by the innate immune system through the mannose binding lectin (MBL), immunomodulating several immune responses (Torrecillas et al, 2014). Dietary use of MOS has been reported enhancing innate immune parameters in fish, such as white blood cell numbers, phagocytosis, lysozyme and reactive oxygen species (ROS) (Song et al, 2014), and also increasing growth and survival in Dicentrarchus labrax (Torrecillas et al, 2007;, Oncorhynchus mykiss (Staykov et al, 2007), Labeo rohita (Andrews et al, 2009) and Piaractus mesopotamicus (Soares et al, 2018). However, according to the consulted literature, the level of inclusion of MOS in fish diets vary due to the species and few are the studies presenting substantial results in health of Nile tilapia (Sado et al, 2008;Selim and Reda, 2015;Levy-Pereira et al, 2018).…”
Section: Introductionmentioning
confidence: 99%